Mother’s Characteristics, Knowledge and Practices about Children Burn Injury in Sulaimani City - Ibrahem, Abdulrahman M.; Rashed, Kamal J.; Babakir- Mina, Muhammed; Muhamed, Bakhtyar K. (Kurdistan Journal of Applied Research, 2017)
Burn is described as one of the leading causes of injury throughout the world, and is one of the most frequent causes of hospitalization. The aim of this study was to determine mother’s characteristics, Knowledge and practices for burn injuries and burn infection prevention. A cross sectional descriptive study was undertaken in Sulaimani city, Iraq, from October 2015 to July 2016. Participants were evaluated using a structured questionnaire by face-to-face interview. Data were computerized and analyzed using Statistical Package for Social Sciences version 22.0 software. A total of 126 mothers who had burn injury in their children and admitted to burning hospital during the study period, the mean score knowledge of mothers was (3.63), the mean score practice of mothers accounted (4.63), the respondent practice score ranged from (1-8). They had poor, intermediate, and good score knowledge about burns injury and burn infection 79.37%, 18.25%, and 2.38% respectively. In regard to mother’s related practice, there were 66.67% within poor practice level, 30.95% of an intermediate level, and 2.38% had a good practice level. The study shows that mother knowledge and practice in Sulaimani city in relation to burn injury and infection among their children was at a low level and the local health authority should incorporate health education for parents, especially mothers in the prevention of pediatric burn at home involving hot liquid and flames also other domestic hazardous as well as the important activities after burn or pre-hospital admission.